A 'Constitution for the oceans' : the long hard road to the UN Convention on the Law of the Sea / Kirsten Sellars. - Sellars, Kirsten (Cambridge University Press, 2025)
The UN Convention on the Law of the Sea, signed in 1982, was the culmination of half a century of legal endeavour. Earlier attempts to create a treaty regime governing the ocean - at League of Nations and United Nations conferences in 1930, 1958 and 1960 - had all failed to settle the breadth of the territorial sea, and in two cases failed to settle anything at all. During the negotiations, legal concepts were formulated and reformulated: straight baselines inspired archipelagic baselines; fishing conservation zones became exclusive economic zones; innocent passage through straits metamorphosed into transit passage through straits; and the seabed common heritage was replaced by the parallel system of seabed exploitation. Many of the issues that animated the delegates during the negotiations - ocean pollution, over-fishing, naval mobility, continental shelf claims and the impact of seabed mining - continue to exercise policymakers and lawyers to this day.